(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper presents a group of inscriptions made on pottery, recovered in various archaeological excavations carried out in Valentia (Valencia, Spain), in the last decades. It includes sixteen Latin documents, three Greeks, one Iberian and five signs, all of them dated between the last quarter of the second century B.C. and destructión of the city during the Sertorian Wars.